Animation Videos as a Medium for Information in Introducing the Tradition of Ratu Brutuk - I Gusti Putu Made Dwija Semarayasa; Putu Satria Udyana Putra; Dwi Novitasari; I Wayan Adi Putrayasa; I Nyoman Widhi Adnyana (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2025)
This research develops a two-dimensional animation as an educational medium to introduce and preserve the Ratu Brutuk tradition of Trunyan Village, Bangli, Bali. The impetus for this study lies in the limited understanding among youth regarding the significance and history of the Ratu Brutuk tradition, compounded by the lack of appealing informational media. Data were gathered through direct observation, in-depth interviews with key figures, and questionnaires. Production followed structured stages, encompassing pre-production, production, and post-production, with a focus on combining narrative, illustrative visuals, and culturally authentic audio. Evaluation included media and content experts as well as a target audience of young viewers, all of whom gave high ratings to the animation’s effectiveness. The results indicate that 2D animation serves as an effective platform for raising awareness and cultivating interest in the safeguarding of local traditions among younger generations.